Crescimento e marcha de absorção de nutrientes no feijoeiro cvs. BRS-MG talismã e ouro negro, em plantio direto e convencional - Vieira, Neiva Maria Batista (2006)
The objective of this research was to study the growth in height, the dry matter accumulation pattern and also the content, accumulation, absorption march and exportation of nutrients along the bean crop cycle. An experiment was set up in Lavras, MG (winter - spring 2002) and other three were performed in Madre de Deus de Minas, MG (dry crop season - 2005) with bean of cvs. Ouro Negro and Talismã under no-tillage and conventional crop systems. Every seven days 10 or 20 plants had been sampled to height measurements and other 20 plants for dry matter and nutrients content evaluation. The experiments were carried out in a randomized blocks design with three replications and 11 or 12 treatments or sampling times. The data were treated with a variance and regression analysis and representative curves of the evaluated variables were fitted and adjusted. It was observed that the cultivar and the crop system did not show any consistent effect over the final height and the maximal dry matter accumulation in bean perhaps due to the fertility of the soils. The growth curves had shown that the maximum height was reached by the 50 DAE (Days After Emergence) in no-tillage crop system while in the conventional crop system the bean kept growing up to the 72-73 DAE, closing the field later. The pattern of dry matter accumulation showed that there was a small increment until the 21-24 DAE for the two cultivars. The maximum accumulation could be observed in the no-tillage cropping systems by the 75-76 DAE for the cv. Ouro Negro and by the 80-81 DAE for the cv. Talismã. The highest rates of dry matter accumulation were verified by the 45-48 DAE, except for the cv. Ouro Negro in conventional crop system which presented the lowest accumulation rate. The average macronutrients content and their absorption amount were considered at normal levels, except for S that was lower than the normal values. The decreasing order of absorption was N> K> Ca> Mg> P> S, while the one of exportation was N> K> Ca> P> Mg> S. The extractions of N, P, K and Mg were higher in the no-tillage crop system that also presented larger exports of N, P, K and S. Talismã was the cultivar that presented a higher absorption and exportation of Ca while cv. Ouro Negro showed greater K leaf content. The macronutrients N, P, K, Mg and S were absorbed until the 70-80 DAE, while Ca was absorbed until the day 59 and the highest absorption rate of Ca was observed by the 29 to the 37 DAE whereas the other macronutrients were absorbed between 42 and 47 DAE, except S, which presented a larger range in this dates. Besides, the micronutrients contents were considered proper to bean. About the 60 DAE almost all the B, Fe and Mn had already been absorbed, while Cu and Zn were absorbed later, about the 77-79 DAE. The amounts of absorbed micronutrients showed the following decreasing path: Fe> Zn> Mn> B> Cu. Under no-tillage crop system it could be verified a greater absorption of Cu in relation to the conventional bean crop system. The cv. Ouro Negro had shown a higher Fe accumulation in relation to the cv. Talismã. The highest accumulation rates of micronutrients were observed between the 32 and 50 DAE, exception for the cv. Ouro Negro, in conventional crop system which presented the highest rates earlier. In relation to the amounts of micronutrients exported, the sequence were Fe> Zn> Mn> Cu> B.